Stereopsis, Visuospatial Ability, and Virtual Reality in Anatomy Learning. (1st June 2017) - Luursema, Jan-Maarten; Vorstenbosch, Marc; Kooloos, Jan
Abstract : A new wave of virtual reality headsets has become available. A potential benefit for the study of human anatomy is the reintroduction of stereopsis and absolute size. We report a randomized controlled trial to assess the contribution of stereopsis to anatomy learning, for students of different visuospatial ability. Sixty-three participants engaged in a one-hour session including a study phase and posttest. One group studied 3D models of the anatomy of the deep neck in full stereoptic virtual reality; one group studied those structures in virtual reality without stereoptic depth. The control group experienced an unrelated virtual reality environment. A post hoc questionnaire explored cognitive load and problem solving strategies of the participants. We found no effect of condition on learning. Visuospatial ability however did impact correct answers atF ( 1 ) = 5.63 andp = . 02 . No evidence was found for an impact of cognitive load on performance. Possibly, participants were able to solve the posttest items based on visuospatial information contained in the test items themselves. Additionally, the virtual anatomy may have been complex enough to discourage memory based strategies. It is important to control the amount of visuospatial information present in test items.